THE NEED OF CRITICAL LITERACY FOR STUDENTS WHO ARE ACTIVE IN SOCIAL AND POLITICAL ISSUES - Yules Sianipar; Sri Zulfida; Rika Purnama Sari (Prodi Sastra Inggris UKI, 2025)
The use of language that tends to be harsh, sarcastic, and emotional shows how today's young generation articulates their dissatisfaction with public figures, mostly driven by feelings of disappointment with the past of these figures. This case is also related to the domino effect phenomenon, where previous negative events or information about public figures can trigger strong reactions or protests from certain groups. The flower arrangement at UNAIR illustrates how critical literacy, in the context of Indonesian culture that is filled with values of politeness, can be developed as an important skill among young people. This paper examines the answer of the chairman of BEM FISIP UNAIR, Tuffahati Ulayyah from the Harian Surya video podcast script. This study highlights the importance of critical literacy in education, showing that a lack of ability to evaluate and express opinions ethically and responsibly contributes to weaknesses in student critique.